From Riches to Rags, and Back? Institutional Change, Financial Development and Economic Growth in Argentina since 1890. Issue 2 (1st February 2016) - Campos, Nauro F.; Karanasos, Menelaos G.; Tan, Bin
Abstract: Argentina is the only country in the world that in 1900 was 'developed' and in 2000 was 'developing'. Although economic historians have identified and explored various possible explanations (chiefly institutions, political instability, financial development, inflation, trade openness and international financial integration), no study so far has attempted a comprehensive quantitative assessment of their relative importance. This article tries to fill this gap using the power-ARCH framework and annual data since 1896 to study the effects of these factors in terms of both growth and growth volatility. The results highlight two main factors to understand the remarkable growth trajectory of Argentina over the very long run, financial development and institutions (formal and informal political instability) and stress the importance of differences in their short vis-à-vis long-run behaviour.